New and legacy persistent organic pollutants (POPs) in breeding seabirds from the East Antarctic - Phoebe Lewis; Anna Lashko; André Chiaradia; Graeme Allinson; Jeffrey Shimeta; Louise Emmerson (2022)
Persistent organic pollutants (POPs) are pervasive and a significant threat to the environment worldwide. Yet, reports of POP levels in Antarctic seabirds based on blood are scarce, resulting in significant geographical gaps. Blood concentrations offer a snapshot of contamination within live populations, and have been used widely for Arctic and Northern Hemisphere seabird species but less so in Antarctica. This paper presents levels of legacy POPs (polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs) and polybrominated diphenyl ethers (PBDEs)) and novel brominated flame retardants (NBFRs) in the blood of five Antarctic seabird species breeding within Prydz Bay, East Antarctica. Legacy PCBs and OCPs were detected in all species sampled, with Adélie penguins showing comparatively high ∑PCB levels (61.1 ± 87.6 ng/g wet weight (ww)) compared to the four species of flying seabirds except the snow petrel (22.5 ± 15.5 ng/g ww), highlighting that legacy POPs are still present within Antarctic wildlife despite decades-long bans. Both PBDEs and NBFRs were detected in trace levels for all species and hexabromobenzene (HBB) was quantified in cape petrels (0.3 ± 0.2 ng/g ww) and snow petrels (0.2 ± 0.1 ng/g ww), comparable to concentrations found in Arctic seabirds. These results fill a significant data gap within the Antarctic region for POPs studies, representing a crucial step forward assessing the fate and impact of legacy POPs contamination in the Antarctic environment.